Pemanfaatan Semen Slag untuk Stabilisasi Tanah dan Pengaruhnya Terhadap Nilai CBR Berdasarkan Variasi Kadar Air Sisi Basah Optimum - Enden Mina; Woelandari Fathonah; Rama Indera Kusuma; Naufal Abdurrasyid (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2021)
Many of the damage in road construction occurred because the soil did not have a good bearing capacity, therefore soil improvement was needed to increase the strength of the soil. One of the damaged roads that occur due to the lack of soil bearing capacity is at Priyayi Mosque Village Road, Kasemen District, Serang City which has a low carrying capacity with a CBR value of 1.99%. In this study, several tests were carried out, soil physical and California Bearing Ratio test. Soil physical tests carried out were water content, soil density, grain size analysis, Atterberg limits, compaction test and, CBR with the addition of slag cement with variations of 0%, 5%, 10%, 15% based on Variation of optimum wet side moisture content. The result of soil physical properties testing obtained the type of soil is an organic clay with high plasticity. The results of the California Bearing Ratio test on the original soil had a CBR value of 2.4% and there was an increase to the optimum at the addition of 15% Slag Cement in 0 and 3 days of curing with a CBR value of 11.2% and 15.25%. Based on these results, it can be concluded that the cement slag content of 15% with 3 days of curing time can increase the bearing capacity of the soil and fulfill the requirements as a good road subgrade